2014
DOI: 10.1103/physreve.90.032914
|View full text |Cite
|
Sign up to set email alerts
|

Controlling synchrony in oscillatory networks via an act-and-wait algorithm

Abstract: The act-and-wait control algorithm is proposed to suppress synchrony in globally coupled oscillatory networks in the situation when the simultaneous registration and stimulation of the system is not possible. The algorithm involves the periodic repetition of the registration (wait) and stimulation (act) stages, such that in the first stage the mean field of the free system is recorded in a memory and in the second stage the system is stimulated with the recorded signal. A modified version of the algorithm that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Recently we have applied this algorithm to monostable oscillatory networks, which possess stable coherent and unstable incoherent states, and shown that it can effectively stabilize the incoherent state [35]. Now we verify the capability of this algorithm to switch a bistable network from the stable coherent state to the stable incoherent state.…”
Section: Eliminating Synchronization Via An Act-and-wait Algorithmmentioning
confidence: 91%
See 3 more Smart Citations
“…Recently we have applied this algorithm to monostable oscillatory networks, which possess stable coherent and unstable incoherent states, and shown that it can effectively stabilize the incoherent state [35]. Now we verify the capability of this algorithm to switch a bistable network from the stable coherent state to the stable incoherent state.…”
Section: Eliminating Synchronization Via An Act-and-wait Algorithmmentioning
confidence: 91%
“…Now we verify the capability of this algorithm to switch a bistable network from the stable coherent state to the stable incoherent state. As applied to neural networks, the act-and-wait algorithm is formulated as follows (see [35] for details). It is assumed that only mean field of the network is available for observation and only homogeneous perturbations are allowed.…”
Section: Eliminating Synchronization Via An Act-and-wait Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of more sophisticated methods to avoid synchronization of interacting oscillators in general and more specifically with the possible application to neuronal arrays have been described in literature, for example [33,37,[44][45][46][47][48][49][50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%